HEPATOTOXIC IMPACT OF ERYTHROMYCIN SUCCINATE AFTER ORALLY REPEATED EXPOSURE IN MALE ALBINO SWISS MICE (Mus musculus) - & Taher, Timimi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The present study was aimed to determine the effects of erythromycin on the liver of albino Swiss mice. The study sample included 12 male mice divided into 3 groups. Mice of groups 1 and 2 were orally administrated with a daily dose 50 and 100 mg/kg bw erythromycin, respectively, while group 3 served as control and administrated with 0.1 ml distilled water. The treatment continued for 14 days . The results indicated a significant increase (p